Graphene-wrapped nitrogen-doped hollow carbon spheres for high-activity oxygen electroreduction. (11th June 2018) - Ma, Ruguang; Xing, Ruohao; Lin, Gaoxin; Zhou, Yao; Liu, Qian; Yang, Minghui; Hu, Chun; Yan, Kang; Wang, Jiacheng
Abstract : An effective "plane-to-point" conductive network formed via wrapping N-doped hollow carbon spheres with graphene nanosheets could effectively promote fast electron transfer to the active sites, obtaining enhanced activity for electrocatalytic oxygen reduction. Abstract : Graphene wrapping could be used to improve the electrochemical performance of electrodes via the formation of an effective "plane-to-point" conductive network to promote fast electron transfer to the active sites. In this paper, a series of N-doped hollow carbon spheres wrapped by flexible graphene nanosheets (NGCs) have been successfully prepared by the self-assembly of graphene oxide nanosheets onto the surface of hollow polymer spheres, followed by pyrolysis in flowing ammonia. The as-synthesized NGCs show unique hierarchical nanostructures, large hollow cores, large surface areas, and high relative contents of pyridinic and graphitic N groups, as well as uniform wrapping of graphene layers outside of the carbon spheres. The metal-free NGCs show much better activity for the electrocatalytic oxygen reduction reaction with a larger limiting current density and lower onset potential than those without graphene wrapping. They also showed superior long-term stability and fuel crossover effect to commercial Pt/C. These results indicate that graphene wrapping is an effective strategy for improving the activity of electrocatalytic materials via constructing a fast electron transfer network.